Comparative analysis of a complement fixation assay and enzyme immunoassay to determine the seroprevalence of measles and varicella in a survey of healthcare workers - Shibata, Hiroshi; Kumakura, Shunichi; Isobe, Takeshi; Hirose, Masahiro; Ohe, Miki; Nishimura, Nobuhiro; Onoda, Keiichi; Nagai, Atsushi; Yamaguchi, Shuhei (Journal of international medical research, 2013)
Objective Seroprevalence surveys of healthcare workers for vaccine-preventable diseases, including measles and varicella, are essential for disease prevention and infection control programmes. The purpose of this study was to compare the complement fixation (CF) assay and an enzyme immunoassay (EIA) to determine the prevalence of immunoglobulin G antibodies directed against measles and varicella viruses in healthcare workers. Methods Antimeasles and antivaricella antibody titres were measured simultaneously in serum samples from healthcare workers employed at a Japanese university hospital, using the CF assay and an EIA. Results Serum samples were obtained from 898 healthcare workers. Seropositivity rates determined using the CF assay and EIA were 67.8% versus 94.0%, respectively, for measles, and 83.2% versus 97.6% for varicella. Compared with EIA, a nine- and 22-fold higher number of seronegative subjects was identified by the CF assay for measles and varicella, respectively. Conclusion Differences between the CF assay and EIA in detecting seronegative or seropositive healthcare workers for measles and varicella suggest that undertaking a seroprevalence survey using an EIA, rather than a CF assay, would more accurately determine susceptibility to vaccine-preventable diseases, in healthcare settings.